2017
DOI: 10.1371/journal.pcbi.1005810
|View full text |Cite
|
Sign up to set email alerts
|

Distinct prediction errors in mesostriatal circuits of the human brain mediate learning about the values of both states and actions: evidence from high-resolution fMRI

Abstract: Prediction-error signals consistent with formal models of “reinforcement learning” (RL) have repeatedly been found within dopaminergic nuclei of the midbrain and dopaminoceptive areas of the striatum. However, the precise form of the RL algorithms implemented in the human brain is not yet well determined. Here, we created a novel paradigm optimized to dissociate the subtypes of reward-prediction errors that function as the key computational signatures of two distinct classes of RL models—namely, “actor/critic”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 75 publications
2
65
1
Order By: Relevance
“…This stands in contrast to our finding that classifier accuracy in two striatal regions distinctly correlated with two behavioral measures of learning during Pavlovian conditioning. While we did not predict an absence of a correlation between classifier accuracy in OFC and behavioral measures, it is nevertheless interesting to speculate how this finding relates to previous findings 53,54 . One possible explanation is that while the OFC is involved in encoding the relationship between stimuli and expected reward, as well as in encoding stimulus–stimulus associations, these representations are not directly utilized to drive behavior in the OFC.…”
Section: Discussioncontrasting
confidence: 88%
“…This stands in contrast to our finding that classifier accuracy in two striatal regions distinctly correlated with two behavioral measures of learning during Pavlovian conditioning. While we did not predict an absence of a correlation between classifier accuracy in OFC and behavioral measures, it is nevertheless interesting to speculate how this finding relates to previous findings 53,54 . One possible explanation is that while the OFC is involved in encoding the relationship between stimuli and expected reward, as well as in encoding stimulus–stimulus associations, these representations are not directly utilized to drive behavior in the OFC.…”
Section: Discussioncontrasting
confidence: 88%
“…Such transfer is related to striatal correlates of learned value . While our in-task learning measures are related to ("Yes" / "No") action value, this previous work and recent human fMRI research indicate that mechanisms supporting the learning of stimulus-action and stimulus-value associations operate at the same time (Colas et al, 2017).…”
Section: Participants and Overview Participants Were Recruited Via Amentioning
confidence: 57%
“…Another study, with the CIT168 atlas as reference, combined electrophysiological, lesion, and functional MRI data, and found evidence that the human amygdala processes both the degree of emotion in facial expressions and the categorical ambiguity of the emotion shown, and that these two aspects of amygdala processing can be most clearly distinguished at the level of single neurons [10]. The present extension of the CIT168 has already been used in a recent functional MRI study, which found evidence for state value prediction errors in the human substantia nigra (pars compacta), while participants solved a Markovian decision making task [11].…”
Section: Background and Summarymentioning
confidence: 85%